Thyroid Dysfunction After Intensity-Modulated Radiotherapy and PD⁃1 Inhibitor Treatment for Locally Advanced Nasopharyngeal Carcinoma - Shang K; He Q; Xu X; Luo X; Zhao C; Liu L; Li Z; Li Y; Jin F (Therapeutics and Clinical Risk Management)
Kai Shang,1,2,* Qianyong He,1– 3,* Xinyu Xu,2 Xunyan Luo,2 Chaofen Zhao,1,3 Lina Liu,1– 3 Zhuoling Li,1– 3 Yuanyuan Li,1– 3 Feng Jin1,3 1Department of Oncology, the Affiliated Hospital of Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China; 2School of Clinical Medicine, Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China; 3Department of Oncology, the Affiliated Cancer Hospital of Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Feng Jin, Department of Oncology, the Affiliated Hospital of Guizhou Medical University, 28 Guiyi Street, Guiyang, Guizhou, 550004, People’s Republic of China, Tel +851-86512802, Email tjzlk2023@163.comPurpose: Analyze the incidence and risk factors of thyroid dysfunction in patients with advanced nasopharyngeal carcinoma (LA-NPC) after intensity-modulated radiotherapy (IMRT) and PD⁃1 inhibitor treatment and their relationship with treatment efficacy and prognosis.Methods: Eighty-five LA-NPC patients treated with IMRT and PD-1 inhibitors were retrospectively collected from March 1, 2019, to May 30, 2022. The incidence of thyroid dysfunction after combination therapy was analyzed. The Kaplan–Meier method was used to analyze the relationship between thyroid dysfunction and patient prognosis. Logistic regression analysis was used to screen independent risk factors for thyroid dysfunction.Results: As of data cutoff (May 31, 2024), the median follow-up time was 27.8 months (range: 25.6 to 32.0 months). The median time of onset of thyroid dysfunction was 8.26 months. The incidence of thyroid dysfunction is 47.06% (40/85), with clinical hypothyroidism being the main cause at an incidence rate of 28.24% (24/85) and clinical hyperthyroidism at an incidence rate of 3.53% (3/85). The incidence of grade 1 thyroid immune-related adverse events (irAEs) was 29.41% (25/85), and the incidence of grade 2 thyroid irAEs was 17.65% (15/85). Patients with thyroid dysfunction had longer overall survival, progression-free survival, and distant metastasis-free survival at both one and two years compared to patients with normal thyroid function, but the difference was not statistically significant (p > 0.05). Multivariate logistic regression analysis showed that pretreatment lactate dehydrogenase (LDH) (p = 0.079) is an independent predictor of thyroid dysfunction after radiotherapy in combination with immunotherapy for LA-NPC.Conclusion: The study found that the addition of immunotherapy increases the risk and shortens the onset time of thyroid dysfunction in LA-NPC patients treated with chemoradiotherapy. Pretreatment LDH may serve as an independent risk factor for thyroid dysfunction for LA-NPC patients.Keywords: nasopharyngeal carcinoma, IMRT, PD-1 inhibitor, thyroid dysfunction, survival